Calculation possibilities and Eurokod 3 requirements used to calculate internal forces in shell structures - Baran, Wiesław (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
This work presents various types of calculation analysis for shell designing, recommended by Eurokod 3. Analytical solutions for shell groups enabling calculating internal forces for any load are presented. The influence of nonlinear units in geometrical connections on calculation results was analyzed . Necessity of proper researcher preparation to build numerical models of shells and necessity to verify them by analytical models was underlined.